Gender Sensitivity at Judge's Verdicts in Samarinda and Magelang Religious Courts; The Implementation of PERMA Number 03 of 2017 - Lilik Andar Yuni; Murjani Murjani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
Allegedly, some of judge’s verdicts are gender-biased that it makes this an interesting research topic. This paper aims to observe gender sensitivity of judges’ verdicts in Samarinda and Magelang Religious Courts as the implementation of PERMA Number 03 of 2017 during 2017-2019. As empirical normative legal research, this study used a qualitative descriptive method as the data analysis. The findings of research are: First, judges’ verdicts, both in ṭalāq and divorce cases, in Magelang Religious Court showed very good gender sensitivity. The different condition occurred in ṭalāq divorce verdicts at Samarinda Religious Court during 2017 and 2018 although in 2019, it showed a little improvement on gender sensitivity. However, verdicts of divorce lawsuit from 2017 to 2019 did not show likewise and it was very poor in gender sensitivity. Second, in Magelang Religious Court, PERMA Number 03 of 2017 had been very well implemented whereas in Samarinda Religious Court, it did not so as there found no much differences between verdicts before issuence of the PERMA and afterward.(Beberapa putusan hakim dinilai bias gender sehingga topik ini menjadi menarik untuk diteliti. Tulisan ini ingin mengkaji sensitivitas gender dalam putusan hakim di Pengadilan Agama Magelang dan Samarinda serta implementasi PERMA Nomor 03 Tahun 2017 selama 2017-2019. Sebagai penelitian hukum normatif empiris, tulisan ini menggunakan metode analisis data deskriptif kualitatif. Temuan penelitian adalah: Pertama, putusan hakim di Pengadilan Agama Magelang, baik dalam kasus cerai ṭalāq maupun cerai gugat, sudah menunjukkan sensitivitas gender yang sangat baik. Sementara itu untuk Pengadilan Agama Samarinda, putusan cerai ṭalāq pada 2017 dan 2018 tidaklah demikian meski ada sedikit kemajuan dalam hal sensitivitas gender pada putusan-putusan tahun 2019. Buruknya sensitivitas gender juga tampak di berbagai putusan cerai gugat di Pengadilan Agama Samarinda sejak 2017 sampai 2019. Kedua, PERMA Nomor 03 Tahun 2017 sudah terimplementasi dengan sangat baik di Pengadilan Agama Magelang. Namun demikian, hal yang sama tidak ditemukan di Pengadilan Agama Samarinda sebab keberadaan PERMA tersebut tidak berpengaruh signifikan terhadap putusan-putusan yang dikeluarkan sebelum maupun sesudahnya)